Gambaran Tingkat Pengetahuan Ibu Postpartum Primipara tentang Perawatan Payudara di Puskesmas Saronggi - fitriah fitriah; Yulia Wardita; Herlina Alvianti Ningsih (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2020)
ABSTRACT Primipara's post partum maternal knowledge about breast care is still very low. Based on a preliminary study at the Saronggi Health Center, four post partum mothers, especially primipara, found that the mother did not know about breast care, so there were many problems in the process of breastfeeding, such as experiencing milk that did not come out, having nipples that went into, experiencing nipples that did not clean, experience pain when breastfeeding. To prevent these problems by taking care of the breast. The purpose of this study was to determine the level of knowledge of primiparous postpartum mothers about breast care in the Saronggi Community Health Center. This type of research is descriptive with cross sectional approach. The population in this study were all primiparous postpartum mothers registered at the Saronggi Community Health Center on January 13-February 13 2020 by 30 people. The sampling technique used is non probability sampling with accidental sampling method. Analysis of the data in this study used a univariate test. The results of the study are all primiparous postpartum mothers at Saronggi Puskesmas aged 20-35 years by 100%, most primiparous postpartum mothers with high school education were 53.3%, most primiparous postpartum mothers were IRT 83.3% and most postpartum mothers Primipara has less knowledge about breast care by 40%. it can be concluded that the majority of primiparous postpartum mothers in Puskesmas Saronggi have less knowledge about breast care. Suggestions are expected that postpartum mothers can add information and increase knowledge about breast care so as to prevent breastfeeding. Keyword: Knowledge, Postpartum, breastcare